2020
DOI: 10.1016/j.celrep.2020.02.077
|View full text |Cite
|
Sign up to set email alerts
|

miR-181a Modulation of ERK-MAPK Signaling Sustains DC-SIGN Expression and Limits Activation of Monocyte-Derived Dendritic Cells

Abstract: Highlights d miR-181a promotes DC-SIGN expression during terminal mo-DC differentiation d miR-181a limits DC-SIGN + mo-DC responsiveness to inflammatory stimuli d miR-181a fine-tunes terminal mo-DC differentiation by modulating ERK-MAPK signaling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Reduced miR-181a levels in older people are associated with a failure of T cell response against weak antigenic stimuli [ 14 ]. Relevant actions driven by miR-181 were also reported in B cell development as well as in macrophages and dendritic cells, showing anti-inflammatory effects by targeting IL1a [ 26 , 27 ], and confirming its complex role in the immune system development and immune response modulation.…”
Section: Micrornas In the Immune System Developmentmentioning
confidence: 84%
“…Reduced miR-181a levels in older people are associated with a failure of T cell response against weak antigenic stimuli [ 14 ]. Relevant actions driven by miR-181 were also reported in B cell development as well as in macrophages and dendritic cells, showing anti-inflammatory effects by targeting IL1a [ 26 , 27 ], and confirming its complex role in the immune system development and immune response modulation.…”
Section: Micrornas In the Immune System Developmentmentioning
confidence: 84%
“…In our study, it was demonstrated that miR-181A was highly expressed in BMSC-derived exosomes, and miR-181A, miR-181b, miR-181c, and miR-181D jointly formed the miR-181 family, which is one of the most abundant miRNAs in lymphatic tissues [ 39 ]. mir-181a plays an important role in B cell development in bone marrow [ 40 , 41 ] and immune function [ 42 ]. We found that miR-181A can be internalized by CD4 + cells and that miR-181A in CD4 + cells directly target SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, high expression of miR-181a has been shown as one of the features exhibited in iCluster 1 tumours that were associated with a worse prognosis [ 4 ]. However, miR-181a modulation could act via either tumour suppression or oncogene induction via different miRNA targets in different cellular compartments [ 15 , 20 , 21 ]. The roles of miR-181 in tumour initiation and progression and its underlying mechanisms need to be further examined with robust approaches [ 11 , 16 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%